Perancangan Mobile App Digital Marketing Milkyo dengan Metode Prototype Design - Nabawi, Rozan; Tarigan, Brema Gamaliel; Saputra, Prince Bayu; Sukmadiningtyas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research addresses the company's current problems in increasing sales of food and beverage products. Milky Jedot (Jelly Sedot) & Risol Mayo is a business with products that require online marketing to increase sales. Mobile applications are one of the right media used for marketing. Mobile application development needs to be done with the first step, namely the design process. The design method used is prototype design. This method has 6 systematic processes, namely requirements, quick plan, construction prototype design, user evaluation, refinement, and implementation. The utilisation of this method is needed to support the design to be systematic. The result of this research is a mobile application design prototype with quite complex features. The initial process of customers can create an account, then when logged in, the main menu gallery will be seen which can be used to select menus, and cancel menu selections, after which the shopping basket is seen and then enter the payment menu